A blueprint for the fourth generation of Bank of Canada projection and policy analysis models - Donald Coletti (Bank of Canada, 2023)
This paper outlines a strategic plan for the development of the fourth generation of Bank of Canada projection and policy analysis models. The plan features a new Canadian workhorse macroeconomic model as well as a suite of alternative models to better support a risk management approach to monetary policy. This new generation of models seeks to improve our understanding of inflation dynamics, the supply side of the economy and the underlying risks faced by policy-makers coming from uncertainty about how the economy functions. New approaches for dealing with idiosyncratic trends in the data and for leveraging the power of large data sets will be employed.
Keywords: C50; C51; C52; C53; C54; C55; 330; Economic models; Inflation and prices; Labour markets; Monetary policy and uncertainty